2012
DOI: 10.1111/j.1863-2378.2012.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use and Resistance in Animal Farming: A Quantitative and Qualitative Study on Knowledge and Practices among Farmers in Khartoum, Sudan

Abstract: Antibiotic resistance is a major emerging global public health threat. Farmers in the Khartoum state are believed to misuse antibiotics in animal farming leading to daily exposure to resistant bacteria and antibiotic residues. Hence, farmers are at potential risk exposure to bacteria, zoonotic infection and toxicity. We hypothesized that farmers' misuse of antibiotics could be due to their ignorance of the importance of optimal use of antibiotics, the potential health hazards and the economical waste associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 30 publications
9
50
0
Order By: Relevance
“…Education, as expected, was positively associated with knowledge. Eltayb et al (2012) also concluded that higher levels of education were significantly associated with higher levels of knowledge of antibiotic resistance and disease among farmers in Khartoum. Buying antibiotics from a feed-store was also associated with a higher knowledge score, most likely because a farmer who went to purchase antibiotics him/herself may have been more knowledgeable about animal health and confident in his/her ability to treat the disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Education, as expected, was positively associated with knowledge. Eltayb et al (2012) also concluded that higher levels of education were significantly associated with higher levels of knowledge of antibiotic resistance and disease among farmers in Khartoum. Buying antibiotics from a feed-store was also associated with a higher knowledge score, most likely because a farmer who went to purchase antibiotics him/herself may have been more knowledgeable about animal health and confident in his/her ability to treat the disease.…”
Section: Discussionmentioning
confidence: 96%
“…Three herds of cattle belonging to Maasai pastoralists in Kenya were followed for four years by Roderick et al (2000) who reported that oxytetracycline was used at a rate of 0.20–1.00 treatments per animal-year. In Sudan, tetracyclines, penicillins, quinolones and sulfonamide-trimethoprim antibiotics were used in 25, 18, 32 and 4% of treatments (n=73), respectively (Eltayb et al, 2012). In contrast, a survey of large dairy and beef farms in Lima reported that 15 active ingredients were commonly used (Solimano-Maza et al, 2011), while a survey of 113 dairy herds in Pennsylvania reported that 24 different types of antibiotics were used (Sawant et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The farmers’ age was likely to be a proxy for recent education. Low education and poor knowledge of farmers regarding AMU were associated with increased AMR and zoonotic infections in a Sudan study (Eltayb et al, 2012). Both herd characteristics and farm management impact the level of AMU, and explain heterogeneity within farms: for instance, 25% of the French poultry herds consumed between one and two thirds of the total antimicrobial amount (Chauvin et al, 2012).…”
Section: Factors Influencing Antimicrobial Use: the Crucial Issue Of mentioning
confidence: 99%
“…Residents of low-income countries often approach livestock disease treatment using ethnoveterinary medicine (EVM), which encompasses indigenous or “traditional” beliefs, knowledge, skills and practices pertaining to the healthcare of animals [4, 5]. The majority of these societies also rely upon “biomedicine,” defined as the global medical system based upon western scientific principles and products (e.g., antibiotics) [6–9]. Reliance on veterinary biomedicine (VB) has received little anthropological attention [10].…”
Section: Introductionmentioning
confidence: 99%